Monomeric C‐reactive protein induces the cellular pathology of Alzheimer's disease. Issue 1 (8th July 2022) - Gan, Qini; Wong, Alfred; Zhang, Zhengrong; Na, Hana; Tian, Hua; Tao, Qiushan; Rajab, Ibraheem M.; Potempa, Lawrence A.; Qiu, Wei Qiao
Abstract: Introduction: Human study shows that elevated C‐reactive protein (CRP) in blood impacts apolipoprotein E ( APOE ) ε4, but not APOE ε3 or APOE ε2, genotype to increase the risk of Alzheimer's disease (AD). However, whether CRP is directly involved in cellular AD pathogenesis and in which type of neuronal cells of APOE ε4 carriers are unknown. Methods: We aimed to use different primary neuronal cells and investigate if CRP induces cellular AD pathology depending on APOE genotypes. Here the different primary neuronal cells from the different APOE genotype knock‐in mice cortex were isolated and used. Results: Monomeric CRP (mCRP) increased amyloid beta production and, in parallel, induced tau phosphorylation in addition to their related proteins in the primary neurons in a pattern of APOE ε4 >  APOE ε3 >  APOE ε2 in a dose‐ and time‐dependent manner. Consistently, mCRP induced the staining of other neurodegenerative biomarkers, including Fluoro‐Jade B stain (FjB), TUNEL and Cleaved Caspase‐3, in primary neurons in a similar pattern of APOE ε4 >  APOE ε3 >  APOE ε2. In contrast, pentameric CRP (pCRP) had a tendency to induce cellular AD pathology but did not reach statistical significance. On the other hand, it is intriguing that regardless of APOE genotype, mCRP did not influence the expressions of Iba‐1 and CD68 in primary microglia or the expression of glial fibrillary acidic protein in primary astrocytes, and additionally mCRP did not affect the secretions of interleukin (IL)‐1α, IL‐1β, and tumor necrosis factor α from these cells. Discussion: This is the first report to demonstrate that mCRP directly induces cellular AD pathogenesis in neurons in an APOE genotype‐dependent pattern, suggesting that mCRP plays a role as a mediator involved in the APOE ε4‐related pathway for AD during chronic inflammation. Highlights: Pentameric C‐reactive protein (pCRP) can be dissociated irreversibly to form free subunits or monomeric CRP (mCRP) during and after the acute phase. mCRP increased amyloid beta production in the primary neurons in a pattern of apolipoprotein E ( APOE ) ε4 >  APOE ε3 >  APOE ε2 in a dose‐dependent manner. mCRP induced the expression of phosphorylated tau in the primary neurons in a pattern of APOE ε4 >  APOE ε3 >  APOE ε2 in a dose‐ and time‐dependent manner. mCRP plays an important mediator role in the APOE ε4‐related pathway of Alzheimer's disease risk.